The Tea Party in Congress: Ideology and Compromise - Rosenblum, Daniel H. (Tufts Archival Research Center, 2005)
This paper investigates the common portrayal of Tea Party-affiliated members of Congress as uncompromising ideologues. It brings to bear qualitative and quantitative techniques on six different case studies of Congressional votes in addition to broader statistical analysis. Results show that Tea Party Caucus membership is often strongly associated with uncompromising, counter-establishment Congressional voting behavior. However, endorsement by a national Tea Party organization tends not have this same effect. As a group, the "Tea Party freshmen" mostly blend with the rest of the Republican Party"except for their votes on the debt-ceiling controversy. This evidence suggests a more complex nexus between the Tea Party movement and Congress than originally hypothesized.